2017
DOI: 10.1097/md.0000000000007369
|View full text |Cite
|
Sign up to set email alerts
|

A case report of hyperosmolar hyperglycemic state in a 7-year-old child

Abstract: Rationale:A hyperosmolar hyperglycemic state (HHS) is a rare presentation of a hyperglycemic crisis in children with diabetes mellitus. As this condition can be fatal and has high morbidity, early recognition and proper management are necessary for a better outcome. Here, we report a rare case of HHS as the first presentation of type 1 diabetes mellitus (T1DM) in a 7-year-old girl.Patient concerns:The patient was admitted due to polyuria and weight loss in the past few days. The initial blood glucose level was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 17 publications
1
8
0
Order By: Relevance
“…Undiagnosed diabetes mellitus, most often type 2, with underlying infection is the most common cause of HHS, as it was in the presented case [1]. It is, however, still an unusual presentation of type 2 diabetes in children, found in 2% of cases, developing due to diagnosis delay, which also occurred in our patient [3][4][5]. Recent studies showed an increase of HHS prevalence in the paediatric population [6,7]; it is therefore important to know how to diagnose and treat this condition.…”
Section: Discussionsupporting
confidence: 49%
See 1 more Smart Citation
“…Undiagnosed diabetes mellitus, most often type 2, with underlying infection is the most common cause of HHS, as it was in the presented case [1]. It is, however, still an unusual presentation of type 2 diabetes in children, found in 2% of cases, developing due to diagnosis delay, which also occurred in our patient [3][4][5]. Recent studies showed an increase of HHS prevalence in the paediatric population [6,7]; it is therefore important to know how to diagnose and treat this condition.…”
Section: Discussionsupporting
confidence: 49%
“…It is believed to be associated with a delay in the diagnosis of these diseases. Mortality in the course of HHS reaches 20-30%, and it is approximately 10-times higher than in diabetic ketoacidosis (DKA) [3,4].…”
mentioning
confidence: 99%
“…Cho et al reported HHS as the first presentation of type 1 DM in a 7-year-old girl 11. Although she appeared cachectic, her mental status was normal.…”
Section: Discussionmentioning
confidence: 99%
“…The mortality rate in patient with HHS varies between 20% and 60% and timely diagnosis as appropriate treatment prevent complications and death. 2,3,17 The child presented with hyperglycaemia without acidosis, which could have led to a delayed diagnosis of diabetes 1. Contrary to diabetic ketoacidosis, HHS is characterized by development of a severe hyperglycaemia without acidosis, these patients maintain a low insulin production leading to the absence or underproduction of ketones via lipolysis.…”
Section: Discussionmentioning
confidence: 99%